Confirmation of Safety of Titanium Wire in Sternotomy Closure, A Randomized Prospective Study - Eraqi, Mohamed; Diab, Abdel Hannan; Matschke, Klaus; Alexiou, Konstantin (The Thoracic and Cardiovascular Surgeon, 2023)
Background There are many factors that are known to increase the risk of sternal wound infection (SWI); some studies have reported that nickel is a risk factor for SWI. Titanium wires have only been used as an alternative to steel wires in patients with known allergy to nickel. However, there is a paucity of literature regarding the safety of using titanium wires compared to that on the safety of steel wires for sternum closure after cardiac surgery. Therefore, this study aimed to demonstrate the noninferiority of titanium wires, even in patients without a known allergy.Methods A total of 322 patients who underwent elective full median sternotomy were randomly assigned to sternal closure either by titanium wires (n = 161) or by stainless steel wires.Results Fourteen patients had sternal instability, six (3.7%) patients in the titanium group and eight (5%) patients in the stainless steel group (p = 0.585). There was no statistically significant difference between both groups in terms of postoperative wound infection (p = 0.147). Patients in the titanium group experienced statistically significant lower postoperative pain than those in the stainless steel group (p = 0.024). The wire type was not an independent risk factor for SI, as shown by univariate and logistic regression analyses.Conclusion Titanium wires are a good alternative and have been proven to be safe and effective for sternal closure. The surgeon should be aware of the possibility of developing an allergic reaction to the wires, especially in patients with previous multiple allergic histories.
Keywords: titanium wires; nickel allergy; sternal instability; sternotomy closure